POTENSI DAN PROSPEK PENGEMBANGAN HUTAN RAKYAT DI KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Anwar, . (Universitas Tadulako, 2018)
Construction and development of community forests is one of the objectives of forest programmes increased to meet the needs, in addition to timber from natural forests and forest plantations. The deficit of constant demand for wood is one of the opportunity to development and build of community forests. One of the developed forest is planted with local plants species as nyatoh and palapi in Parimo, Central Sulawesi.The research objective were to analyze the potential of community forest production, to calculate and to analyze the needs of wood as raw material for industries and reviewing, analyzing the prospects of raw materials availability from the community forest to fulfill the needs of industrial raw materials. The research was conducted in the villages of Suli and Beraban Moutong Balinggi Parigi Subdistrict of Central Sulawesi during the four months from March to June 2014. The results showed that the potential total production of nyatoh combined with chocolate was the highest compared with all these combinations, palapi combined with chocolate, nyatoh with palapi and chocolate as well as palapi with nyatoh andÂ chocolate. This difference was caused by mean annual increment (MAI) of Nyatoh 2.7 m3 higher than the MAI of Palapi 1.87 m3/ha/tahun. The real average requirement of raw materials per year in Parigi Subdistrict for timber industry was 12,517 m3/ha, while the ability of community forests to supply raw materials was only 3635 m3/ha. Therefore, for the fulfillment of industrial raw materials supplied from the community forest instead of the raw material from natural forests should be realized as much as 8,882 m3/ha. The results of the correlation regression analysis 0.7 indicated that for the fulfillment of the raw material of wood industry in Parigi Moutong Subdistrict has a very large prospects of community forest development.Based on this research it may be suggested that the development of the community forests to achieve a high volume of production requires a combination of nyatoh and chocolate with a spacing of 6 m x 6 m. With regard to the existing potential, then it is time that the Government of District Parigi Moutong made regulations on the development of community forests, as the rule of Minister of Forestry number: P.26/Menhut-II/2005, the Central Government, Provincial, District/City Government should develop a rights on forests through the institutional development and business systems, so that communities are self-reliant and capable in the use of the forest and independent in the conduct of a business through a fascilities such as mentoring, training, counselling, provision of information or the provision of capital assistance and other incentives.